The relationship between the psychological conditions of dental and oral health workers during the PPKM level-4 period of the Covid-19 pandemic at the Makassar city hospital: Online cross-sectional survey: Hubungan kondisi psikologi tenaga kesehatan gigi dan mulut selama periode PPKM level-4 pandemi Covid-19 di rumah sakit kota Makassar: Survei cross-sectional secara online - Ayub Irmadani Anwar; Burhanuddin Daeng Pasiga; Rasmidar Samad; Rini Pratiwi; Nur Syamsi; Fuad Husain AKbar (Makassar Dental Journal, 2022)
To determine the relationship between the psychological conditions of dental and oral health workers during the Covid-19 pande-mic, it was conductedobservational analytic study, with a cross-sectional design by online. A total of 156 dental health workers at RSGMP Unhas and RSKDGM who worked during thePPKM period 26 July 2021-6 September 2021 were obtained using the purposive sampling technique. This study was conducted using a questionnaire instrument in the form of an online google form in November 2021. The questionnaire consisted of 19 question items using the Kruskal Wallis test and Mann Whitney test.The results showed that gender and work experience had a significant effect on infection. Female participants were more likely to be concerned about thepresence of infection and that the virus was imminent. It is concluded there was a significant relationship between the psychological condition of dental and oral health workers during the COVID-19 pandemic, mainly women, and doctors with less work experience, reporting a much higher impact.